Tracking movements in an endangered capercaillie population using DNA tagging - Bañuelos, María José (2024)
Knowing the location and movements of individuals at various temporal and spatial scales is an important facet of behavior and ecology. In threatened populations, movements that would ensure gene flow and population viability are often challenged by habitat fragmentation. Also in those endangered populations capturing and handling individuals to tag them, or to obtain tissue samples, can present additional challenges. DNA tagging, i.e. non-invasive individual identification of samples, can reveal movement patterns. We used fecal material genetically assigned to individuals to indirectly track movements of a large-bodied, endangered forest bird, Cantabrian capercaillie (Tetrao urogallus cantabricus). We wanted to know how the birds were using the fragmented forest landscape, and whether they showed fidelity to display areas. We used multi-event capture−recapture models to estimate fidelity to display areas among three consecutive mating seasons. We identified 127 individuals, and registered movements of 22 females and 48 males. Most observed movements were as expected relatively short, concentrated around display areas. We did not find differences in movement distances between females and males within mating seasons, or between them. Fidelity to display areas among seasons was 0.62 (± 0.12 SE) for females and 0.77 (± 0.07 SE) for males. The best CR model suggested no sex or season effects. Several longer movements, up to 9.9 km, linked distant display areas, demonstrating that Cantabrian capercaillies were able to move between different parts of the study area, complementing previous studies on gene flow. Those longer movements may be taking birds out of the study area, and into historical capercaillie territories, which still include substantial forest cover. The non-invasive DNA tagging approach provided a much larger sample size than would have been feasible with direct tracking. Lack of information on the social status of individuals, and timing of movements, are some disadvantages of DNA tagging.